Pengaruh Pemberian Tepung Daun Kersen Terfermentasi Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super - Kristina Ratnasari Antu; I Gusti Agus Putra Sanjaya; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2026)
The need for nutritious food products, especially food products of animal origin, is currently increasing. This is in line with increasing public awareness of the importance of animal protein for health. One of the commodities that can be developed is super free-range chicken. The purpose of this study is to determine the effect of giving fermented kersen leaf flour in rations on the carcass of 10-week-old super free-range chickens and to find out what percentage of the level of fermented kersen leaf flour in the ration is able to give the best results to the carcass fragments of 10-week-old super free-range chickens. The strategy of providing local feed as a source of chicken feed is designed to utilize feed materials that are easily available and reduce the cost of purchasing feed materials, without affecting the productivity of super free-range chickens. Therefore, the way that can be done is to use alternative feed ingredients, namely kersen leaves which are widely available and easy to get. The Research Design used in this research is a Complete Random Design (RAL) consisting of 5 treatments and 3 replicas of K0 = Control ration without the addition of fermented kersen leaf flour. K1 = A ration containing 3% fermented kersen leaves. K2 = A ration containing 6% fermented kersen leaves. K3 = A ration containing 9% fermented kersen leaves. K4 = A ration containing 12 % fermented kersen leaves. From the results of the research that has been carried out, the administration of fermnerated kersen leaf flour in the ration of super free-range chickens has an unreal effect (P>0.05) on all observed variables (chest weight, thigh weight, back weight and super free-range chicken wing weight). Giving fermented kersen leaf flour at a level of 12% in rations can show the best results against the fragmentation of super free-range chicken carcasses.